Phosphate Solubilizing Microorganism and available P on the Rizosphere of some Ages and Distances from the Center of Maize Roots - Ainin Niswati; Sri Yusnaini; Mas Achmad Syamsul Arif (JOURNAL OF TROPICAL SOILS, 2008)
Effect of the age and root distance of maize on the population of phosphate solubilizing microorganisms was studied. The rizosphere and non-rhizosphere soil of maize was setup in the special pots with dimension of 60 cm x 60 cm x 30 cm in the glasshouse.  The Ultisols soil was planted with maize until the vegetative stages. The results showed that  on the distance of  > 20 cm from center of roots, the age of maize increase the population of phosphate solubilizing microorganisms.  The population of phosphate solubilizing microorganisms in the rhizosphere soil was 8 - 23× more than from those non-rhizosphere soils. On the distance of 0-10 cm, the age of maize affected the number of phosphate solubilizing microorganisms in the rizosphere and non-rhizosphere soil. Available-P (Bray I) was affected by the age and distance of root maize.  The highest value was observed on the 7 weeks after planting at a distance of >20 cm.  Available P was significantly higher in the rhizosphere soil than that in non-rhizosphere soil, especially at a distance of >20 cm on the 7 weeks after planting.  The positive correlation was occurred between phosphate solubilizing microorganism and the value of available-P, soil pH, organic C and total N.